Cinq langues de la Colombie britannique; Haïda, Tshimshian, Kwagiutl, Nootka et Tlinkit. ... - La Grasserie, Raoul De, 1839-1914 (University of Victoria Libraries, 2021)
Written in French and focuses on the grammar and usages of five languages in British Columbia namely: Haida, Tshimshian, Kwagiutl, Nootka, and Tlinkit. ...